Javanese Cultural Socialization in Family and Ethnic Identity Formation of Javanese Adolescent Migrant at Lampung Province - Aryanti, Nina Yudha (Universitas Negeri Semarang, 2015)
Javanese adolescent migrants interactions in family across generations at multicultural society in Lampung stimulates a dynamic atmosphere Â for adolescent ethnic identity formation. Through socialization, the adolescent acquires Javanese cultural information as a foundation to develop their ethnic identity. This research aims are to know, find and analyze the cultural socialization aspects in family that support ethnic identity formation of Javanese adolescent migrants in Lampung. Throughout qualitative research, this research showed that socialization and ethnic identity formation in family is based on six themes : (1) family migration history; (2) adopted and referred family culture; (3) family identity development; (4) parenting style and Â amount of time spend for interaction in family and parentâ€™s type of job ; (5) language used within the family; and (6) situations that support and obstruct of expression of ethnic identity.